Cover Image. (27th September 2020) - Fan, Jiahui; Liu, Zhenqiu; Mao, Xianhua; Tong, Xin; Zhang, Tiejun; Suo, Chen; Chen, Xingdong
Abstract : The cover image is based on the Original Research Global trends in the incidence and mortality of esophageal cancer from 1990 to 2017 by Jiahui Fan et al., https://doi.org/10.1002/cam4.3338 .